PENENTUAN KADAR ASAM AMINO ESENSIAL (FENILALANIN, TREONIN, TIROSIN DAN VALIN) PADA TELUR PENYU DAN TELUR AYAM RAS - Agnes Lebang; Saibun Sitorus; winni astuti (JURNAL KIMIA MULAWARMAN, 2018)
Determination of amino acid essential’s content (phenylalanin, threonin, tyrosin and valine) on turtle eggs and chicken eggs. Turtle eggs and chicken eggs are a high animal protein source and easy to obtain. This research has been carried out by categorizing of turtle eggs and chicken eggs by size and continued analysis of water content by Methods of Gravimetry, analyzes protein content total by the Method of Kjeldahl and analysis of the levels of essential amino acids with Method of HPLC (High Performance Liquid Chromatography). In this study, the researcher found the water content in the mix (large, medium and small) is 73,1891% and mixture of chicken eggs of different size is 73,1820%. Results of total protein content with used Kjeldahl method mixture based on the size of turtle eggs is 9,3114% and mixture chicken eggs is 10,2691%. Results of the amino acid content with used HPLC (High Performance Liquid Chromatography) method on a mixture of turtle eggs is Phenylalanin 1,69%, Threonin 1,16%, Tyrosin 2,46% and Valine 1,46%. Mixture of chicken eggs is Phenylalanin 0,30%, Threonin 0,61%, Tyrosin 1,03% and Valine 0,55%